1287 THE VALUE OF A MULTIDISCIPLINARY TEAM (MDT) IN MANAGING PATIENTS WITH COMPLEX OR UNEXPLAINED SYNCOPE. (16th January 2023) - McCall, R; Anderton, L; Mitchell, L
Abstract: Introduction: Syncope is a common clinical problem with a lifetime prevalence of 20%. 1 Syncope shares clinical features with other disorders including seizures, metabolic disturbances and sleep disorders. 2 The assessment and management of syncope can be challenging. The syncope service at the QEUH is run by geriatricians and cardiologists with an interest in syncope. Although MDTs are recognised key components in contemporary patient care in areas such as heart failure and cancer management, there is no guidance on MDT working in syncope management. 3/4 In November 2017, a syncope MDT was introduced at the QEUH involving cardiologists, geriatricians, a neurologist and cardiac physiologists. This in-person MDT occurs monthly with outcomes recorded on electronic medical records in addition to a database. The aim of this review was to understand the potential impact of the MDT on diagnostic yield and time to further investigation or management. Method: A retrospective case note analysis was performed for patients reviewed at the Syncope MDT between November 2017 and December 2021. Results: 103 patients were discussed with an average age of 64 years. The main reason for referral was cardiology specialist advice (65%), neurology specialist advice (19.4%) and complex case review (13.6%). After MDT discussion, the percentage of patients with unexplained TLoC reduced from 26.2% to 14.6% without requirement for additional investigations. 8.7% of patients were started on anti-epileptic medication prior to outpatient neurology review after a diagnosis of seizure disorder was established and 23.1% of patients were streamlined for pacemaker or ILR insertion. Conclusion: Introduction of a syncope MDT reduces unexplained syncope rates in complex patients, streamlines investigations, reduces the need for multi-speciality outpatient reviews and allows earlier introduction of anti-epileptic medication for those with a new seizure disorder. These benefits improve the patient experience by reducing time to diagnosis and treatment.